The idea factory : Bell Labs and the great age of American innovation - Gertner, Jon (Penguin Press, 2012)
Highlights achievements of Bell Labs as a leading innovator, exploring the role of its highly educated employees in developing new technologies while considering the qualities of companies where innovation and development are most successful.